KOMPAS (Komik Pubertas) Learning Media Development Based on the Qur'an and As-Sunnah for Elementary School Students - Azmi Al Bahij; Dhita Sufi Dzul'arfah (Universitas Pendidikan Indonesia (UPI), 2022)
Development Learning Media KOMPAS (Comic Puberty) based on Al-Quran and As-Sunnah for Elementary School is research beside deficiency learning media that discusses puberty subjects in elementary school. The purpose of this research is to find out student responses about the attractiveness of learning media KOMPAS (Comic Puberty) based on Al-Quran and As-Sunnah by developing learning media of KOMPAS. The research method used (Research and Development) and the development model used the Rowntree development method. This learning media has been developed and has been validated by material experts, linguist experts, and media experts. This Development method has two stage trials, face to face tryouts learners and field tryouts. The result of the language validation test reached 98%, material validation reached 92% and media validation reached 86%. The result of student responses about the attractiveness of learning media was reached 100%. Based on this data, this learning media KOMPAS (Comic Puberty) based on Al-Quran and As-Sunnah is valid and attractive for students in elementary school .